REPUBLIC OF RECOGNITION APPLICATIONS INDONESI PRESIDENTIAL PALACE USING MACROMEDIA DREAMWEAVER MX - Ade Jaja Badruzaman; Rahayu Noveandini, Skom, MM (Jurnal Sistem Informasi, 2006)
At this writing discusses the application of the Republic of Indonesia PresidentialPalace introduction using Macromedia Dreamweaver MX. Application is made withthe purpose of providing information to the public to be aware of the history,functions and building whatever is within the Presidential Palace. Indonesian hasregistered five presidential palace: the palace in Jakarta, Bogor Palace in Bogor,Cipanas in Cipanas Palace, the Palace and the Palace Tampaksiring in Bali GedungAgung Yogyakarta. From history, the Merdeka Palace, Istana Negara, GedungAgung, Cipanas Palace, and the Bogor Palace was built during the Dutchgovernment. Tampaksiring palace built during President Sukarno. PresidentialPalaces is part of a historic building in Indonesia. Perhaps many people will not knowthe history of the Presidential Palace. With this application, it is expected the publicto know some of the nation's history.Bibliography: (